PEMETAAN LOKASI PARIWISATA DAN PENGINAPAN DI PULAU NIAS BERBASIS ANDROID - Novri Krisman; Jimmy Febrianus Naibaho (Universitas Methodist Indonesia, 2018)
The attraction is something that attracts people to visit a certain area. Nias Island has a lot of exotic and interesting tourist areas visited by tourists from home and abroad. However, there are still many tourists who still do not know the location of the tourist and lodging routes. So the purpose of the design of Tourism and Lodging Object Applications in Nias Island based on Android is to make it easier for tourists to search for tourist locations and lodging as well as a navigation tool to find out the route to tourist attractions and lodging. The results of this study will provide a GIS-based Tourist and Lodging Application on Nias Island which is implemented on a Mobile system.